An ethnobotanical study of medicinal plants used by Paniya community of Amarambalam Reserve Forest, Kerala, India - Ashlin Mariam Sam; Ponnusamy, Revathi (Ethnobotany Research and Applications, 2026)
Background: The major tribal communities in Kerala are Paniyar, Kattunayakkan, Aranadans, Paliyan, Irular and Adiyar. Each tribal group has their languages, cultural practices and also have their unique healing methods. Many ethnic communities are still unaware of the importance of documenting their knowledge, which is gradually disappearing with each passing generation. Methods: The study area was located in part of Amarambalam Reserve Forest, which is under the Karimpuzha Wildlife Sanctuary. The objectives were to document indigenous plants used by the Paniya community for medicinal purposes, to record preparation methods, dosages, plant parts used, and additional ingredients. Information was collected among the eleven individuals of the Paniya tribes. Results: Fifty-five plants representing 29 families were documented. Herbs were the most frequently used medicinal plants followed by shrubs, trees and climbers. Euphorbiaceae and Fabaceae members were predominant leaves and whole-plants were more abundantly used in their preparation methods. Additional ingredients included honey, coconut oil, turmeric, milk, salt, or various plant and non-plant-based powders. Paste was the most frequently used formulation method followed by extract, decoction, infusion, powder and juice. Novel medicinal uses for the documented plants were recorded. Conclusions: The analysis of use values and the fidelity levels of plants for specific illness suggests the conservation priorities by identifying the most valuable plants of the community. The collection of ethnobotanical information and documentation of traditional knowledge has also gained prominence from the perspective of drug development. Keywords: Paniya tribes, Kerala, Ethnobotany, Use Value, Fidelity, Ingredients